Study of acute diarrhoea among preschool children from below poverty line families of Lucknow district, North India - Mohammad, Khalid; Gupta, Pratibha (International Journal Of Community Medicine And Public Health, 2018)
Background: Acute diarrheal illness remains one of the major causes of childhood morbidity and mortality especially among children under five in developing countries. Many of the risk factors for contracting diarrheal illnesses are associated with poverty, such as lacking access to safe water and sanitation, poor hygiene practices and unsafe human waste disposal. Objective of the study was to know the prevalence of acute diarrhoea and find out certain associated risk factors among preschool children from below poverty line family of Lucknow district. Methods: A community based cross sectional study was conducted using multistage sampling in rural and urban areas of Lucknow district from August, 2012 to July, 2013. Total 352 children aged 12-47 months from Below Poverty Line families were enrolled in this study. Mothers were interviewed after taking informed consent on pretested predesigned questionnaire. Results: A total of 352 children were participated in this study, of which 75 were suffering from acute diarrhea, thus giving a two-week prevalence of 21.3%. The main risk factors for acute diarrheal illness were found to be Unimproved/no toilet facility, unsafe disposal of children stool, having piped water supply, storage of drinking water at household level, not received complimentary feeding within specified period and no vitamin A supplementation. Conclusions: Approximately one-fifth of the children included in the study reported diarrheal disease. Building toilets and providing safe drinking water at the household level, interventions through effective health education of the community regarding appropriate complimentary feeding and immunization practices may reduce the burden of diarrhoea among these children.